Proposed Corporate Performance Management Using Integrated Performance Management System (IPMS) at PT Pos Indonesia (Persero) - Prilianti, Eliza; Tresnadi Hikmat, Muhammad (International Journal of Engineering and Technology, 2018)
The big market shifting in postal industry begun since a physical letter was being substituted by digitalization of technology, yet it brings new business opportunity in the e-commerce industry. The e-commerce industry in Indonesia is expected to grow by approximately 18% annually in the next five years. It triggers an increasing demand for parcel delivery services. However, the performance of PT Pos Indonesia (Persero) as a State Owned Enterprise engages in postal industry shows the declining trend. The volume of parcel delivery declined during the last three years. The company has not been able to manage its performance due to the incompatibility of performance management system. The purpose of this research is assisting the company to design new performance management system to improve its performance. The Integrated Performance Management System (IPMS) framework is selected because it is able to overcome the issues in the company. There are five stages of IPMS framework includes foundation, background and information, design process, implementation, and refreshment. It consist of three perspectives includes organizational output, internal process, and resources availability. This research proposed the performance management system for Pos Indonesia and produces 20 key performance indicators (KPI) that derived from companyâ€™s vision, mission, and strategy.Â Â